Padrão fermentativo, composição bromatológica e digestibilidade de silagens de cana-de-açúcar inoculadas com aditivo microbiano-enzimático - Reis, Rafael Henrique Pereira dos (2014)
Alcoholic fermentation caused by yeast development is presented as the main limitation of sugar cane silage. The use of additives is employed to alleviate this problem, however, the results on improving the fermentation pattern and bromatological composition are incipient or inconclusive. In this sense, the objective in these study was to evaluate the bromatological composition, in vitro kinetics of gas production, dry matter losses and silage fermentation profile of two varieties of sugar cane treated with microbial-enzymatic inoculant Sil All 4x4® Alltech, Lexington, USA. The additive is an association four bacteria (Enterococcus faecium, Lactobacillus plantarum, Pediococcus acidilactici and Lactobacillus salivarius subs. salivarius) and four enzymes (cellulase, hemicellulase, amylase and pentosanase). Two experiments were executed, the first to evaluate the bromatological composition, fermentation profile and in vitro kinetics of gas production of silages and the second for the evaluate the fermentative losses in ensilage. In both experiments we used a completely randomized design in factorial arrangement 2x2x4 with four replications, being two varieties of sugar cane (early: RB835486 and middle/late: SP79-1011), the presence or absence of the inoculant and four storage times (0, 8, 16 and 64 days of storage). To evaluate the bromatological composition and the in vitro kinetics of gas production were evaluated in the forage and in the silage: the percentage of dry matter (DM), the content of insoluble neutral detergent fiber (NDF), NDF indigestible (NDFi) , contents of mineral matter (MM), crude protein (CP), neutral detergent insoluble protein (NDIP), total digestible nutrients (TDN), in vitro digestibility of organic matter (IVOMD), degradation rates non-fibrous (KdNFC) and fibrous carbohydrates (KdFC). To evaluate the fermentation profile in silage, were evaluated in the silage: pH, contents of soluble carbohydrates (SC), ethanol, volatile fatty acids (acetic acid, propionic acid and butyric acid), losses by effluent (LE) and gas (LG) and dry matter recovery (DMRec). The effects were declared significant at P<0.05. When there was the inoculation effect, was detrimental to the quality of the silage fermentation process and. After 64 days of storage in early variety was reduced DM, KdNFC and increased NDF. Independent of storage time and varieties, the presence of the inoculant reduced the contents of MM, NDIP and coefficient KdFC. The DM, contents of SC, TDN, coefficient of IVOMD and DMRec were reduced over the time of storage, whereas the NDF, GL and EL were increased. It has been observed isolated effect of varieties and your interaction with other factors for most of the variables analyzed, providing greater changes in silages in relation to inoculation. The early variety in the presence of the inoculant showed lower values NDFi, GL and EL, however, also lower values of IVOMD and TDN. Whereas DMRec was not affected by inoculation and varieties singly after 64 days of storage in the presence of the inoculant, the middle/late variety, even with higher values of NDFi, GL and EL, provided silages with higher TDN and IVOMD, in addition higher contents of acetic and propionic acid. Ethanol production was influenced by inoculation and varieties only the 8th days of storage, not differing after 64 days of storage, resulting in high values of DMRec.